Sucrose Phosphate Synthase activity and gene expression in relation to dehydration induced sucrose accumulation in the resurrection plan Xerophyta Humilis - McDonald, Zac Eliot (Department of Molecular and Cell Biology, 2014)
Includes abstract. Includes bibliographical references (leaves 170-198).